Teratoma of ovary in adolescent females – A Clinical and pathological study of 54 cases (Journal of Pharmaceutical Negative Results, 2023)
Introduction: The aim of the study is to evaluate the incidence, frequency and histopathological pattern of the ovarian teratomas. Germ cell tumours represent early 25-30% of the ovarian neoplasms and it varies in respect to their clinical presentation and histopathology.Materials & methods: It is a retrospective & prospective study from the department of pathology at the tertiary health centre. From august 2012 to July 2015, retrieved from the recorded files & analysed. The tissues were fixed in 10% formalin and slides were made with routine hematoxylin & eosin stain.Results: Out of 54 cases, mature cystuc teratoma consitituted 51, 2 struma ovarii and immature teratomas of the ovary. Out of the 54 cases of teratoma, the most common histological type is the most common histological type is mature cystic teratoma.Conclusion: Benign tumours are common than malignant tumours. Mature cystic teratoma is common than immature teratoma. Most of them presented with abdominal pain, even though other presentable symptoms were abdominal lump, irregular bleeding & loss of weight. The most common age group affected was 20-30. Left side was affected more than left side.